2019
DOI: 10.1186/s12915-019-0652-6
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of adult canine intestinal organoids for translational research in gastroenterology

Abstract: Background Large animal models, such as the dog, are increasingly being used for studying diseases including gastrointestinal (GI) disorders. Dogs share similar environmental, genomic, anatomical, and intestinal physiologic features with humans. To bridge the gap between commonly used animal models, such as rodents, and humans, and expand the translational potential of the dog model, we developed a three-dimensional (3D) canine GI organoid (enteroid and colonoid) system. Organoids have recently ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 73 publications
3
113
0
Order By: Relevance
“…We have recently optimized the three-dimensional (3D) in vitro culture conditions of canine primary intestinal organoids and shown that isolated intestinal stem cells differentiate into organoids containing matured intestinal cell lineages within~8 days of culture [9]. The 3D organoid culture technology not only offers a more physiological platform compared with conventional 2D cell lines [10], but also provides a "personalized" modeling to investigate the effect of environmental stimuli or dietary interventions on intestinal epithelium [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently optimized the three-dimensional (3D) in vitro culture conditions of canine primary intestinal organoids and shown that isolated intestinal stem cells differentiate into organoids containing matured intestinal cell lineages within~8 days of culture [9]. The 3D organoid culture technology not only offers a more physiological platform compared with conventional 2D cell lines [10], but also provides a "personalized" modeling to investigate the effect of environmental stimuli or dietary interventions on intestinal epithelium [11].…”
Section: Introductionmentioning
confidence: 99%
“…We envision that our optimized protocol and the robust culture of canine-derived epithelium may enable to develop an advanced in vitro model to demonstrate complex hostgut microbiome crosstalk and pharmacological assessment under various disease milieus. of the primary intestinal epithelium [9]. A colonoid-derived monolayer was generated in a nanoporous insert of the Transwell pre-coated with the extracellular matrix (ECM) mix with Matrigel (100 μg/mL) and collagen I (30 μg/mL) by introducing the dissociated colonoid cells ( Fig 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports showed that mice or rats as experimental models of UC [28] [11,29]. But, dogs share similar environmental, genomic, anatomical, and intestinal physiologic features with humans [30].In this paper, we suggest that cross-bred dogs represents a useful clinical model of UC.…”
Section: Discussionmentioning
confidence: 86%
“…This absence of differentiated cells in expansion medium could not be overcome by prolonged cultivation: low-(≤5) and high-passage (≥10) canine intestinal organoids all tested negative for differentiation marker expression. Recently, Chandra et al published a well-written paper on the derivation of canine intestinal organoids and the presence of goblet and enteroendocrine cells [35]. The formulation of the expansion medium differs in a 5-fold higher concentration of p38-MAPK inhibitor and the addition of 8% fetal bovine serum FBS (Chandra) compared to the medium formulation used herein.…”
Section: Discussionmentioning
confidence: 99%